2022
DOI: 10.1186/s12866-022-02637-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics analysis of a phyllospheric Pseudomonas spp with potential for biological control against coffee rust

Abstract: Background Pseudomonas spp. promotes plant growth and colonizes a wide range of environments. During the annotation of a Coffea arabica ESTs database, we detected a considerable number of contaminant Pseudomonas sequences, specially associated with leaves. The genome of a Pseudomonas isolated from coffee leaves was sequenced to investigate in silico information that could offer insights about bacterial adaptation to coffee phyllosphere. In parallel, several experiments were performed to confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…In a recent study by de Sousa et al. ( de Sousa et al., 2022 ), it was demonstrated that Pseudomonas spp. rely on increased synthesis of exopolysaccharides (EPSs) to cope with osmotic stress and protect cells from desiccation in the phyllosphere.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent study by de Sousa et al. ( de Sousa et al., 2022 ), it was demonstrated that Pseudomonas spp. rely on increased synthesis of exopolysaccharides (EPSs) to cope with osmotic stress and protect cells from desiccation in the phyllosphere.…”
Section: Resultsmentioning
confidence: 95%
“…The biosynthesis of osmoprotectants and the production of EPS enriched in the tested metagenome may reflect adaptations of microbial inhabitants by enhancing attachment to surfaces and offering resistance to environmental pressures and plant defenses (Rastogi et al, 2013). In a recent study by de Sousa et al (de Sousa et al, 2022), it was demonstrated that Pseudomonas spp. rely on increased synthesis of exopolysaccharides (EPSs) to cope with osmotic stress and protect cells from desiccation in the phyllosphere.…”
Section: Abiotic Stress Resistome In Cigar Tobacco Phyllospherementioning
confidence: 99%
“…Biocontrol has been proposed in organic coffee cultivations as an alternative to CLR control. The bacteria of the genus Pseudomonas have generated a great interest in this field because of their benefits for the host plant by producing auxins and siderophores that improve plant development and growth as well as protecting them against phytopathogens [84]. Studies have discovered that Bacillus subtilis and Pseudomonas fluorescens inhibit urediniospore germination and reduce disease incidence and severity.…”
Section: Antagonistic Microorganisms To Hemileia Vastatrixmentioning
confidence: 99%
“…En dicho experimento se evaluaron un total de 234 bacterias endófitas (217) y hongos (17) aislados de tejidos de café. Aunque especies de Pseudomonas también promueven el crecimiento de las plantas y coloniza una amplia gama de ambientes, puede ser un excelente biocontrolador contra la Roya en cafetos ( de Sousa et al, 2022). La creciente preocupación por evitar o reducir el uso de plaguicidas y fertilizantes inorgánicos en el cultivo de café, y optar por alternativas sostenibles y respetuosas con el medio ambiente, ha hecho que entre las investigaciones más demandadas estén el uso de microorganismos y sus compuestos en el manejo de enfermedades como la Roya (Castillo et al, 2022).…”
Section: Manejo De La Enfermedadunclassified